Development and Validation of an Italian Adaptation of the Psychosocial Aspects of Hereditary Cancer Questionnaire - Franiuk, Marzena; Molinari, Elena; Battistuzzi, Linda; Razzaboni, Elisabetta; De Matteis, Elisabetta; Turchetti, Daniela; Godino, Lea; Chiorri, Carlo; Varesco, Liliana (Frontiers in Psychology, 2021)
Individuals that attend cancer genetic counseling may experience test-related psychosocial problems that deserve clinical attention. In order to provide a reliable and valid first-line screening tool for these issues, Eijzenga and coworkers developed the Psychosocial Aspects of Hereditary Cancer (PAHC) questionnaire. The aim of this work was to develop an Italian adaptation of the PAHC (I-PACH). This prospective multicentre observational study included three stages: (i) development of a provisional version of the I-PAHC; (ii) pilot studies aimed at testing item readability and revising the questionnaire; (iii) a main study aimed at testing the reliability and validity of the final version of the I-PAHC with the administration of a battery comprising measures of depression, anxiety, worry, stress, and life problems to 271 counselees from four cancer genetic clinics. Adapting the original PAHC to the Italian context involved adding two further domains and expanding the emotions domain to include positive emotions. While most of the items were found to be easy to understand and score, some required revision to improve comprehensibility; others were considered irrelevant or redundant and therefore deleted. The final version showed adequate reliability and validity. The I-PAHC provides comprehensive content coverage of cancer genetic-specific psychosocial problems, is well accepted by counselees, and can be considered a sound assessment tool for psychosocial issues related to cancer genetic counseling and risk assessment in Italy.